Assessment of Determinants of Technology Development: An Empirical Study - Dixit, Gopal Krishan (Prabandhan: Indian Journal of Management, 2011)
Organizations that want to survive in today’s highly competitive business environment must address the need for high quality, lower costs, and more effective and swifter research and development. These formidable changes have forced the organizations around the world to adopt innovative and state of the art strategies to suitably address the all-important issues of organization survival, growth and excellence. The key driver of organization’s ability to change is innovation. Thus, the organizations are left with no choice but to upgrade the existing systems, products and technologies for their survival. The present work explains that creativity and innovation are the necessary ingredients for developing new technology. The study presents a detailed analysis of the various factors and issues affecting technology development initiatives of tool industry in Patiala region of Punjab state and their relative present status.